Horseshoe crab trace fossils and associated ichnofauna of the Pony Creek Shale Lagerstätte, Upper Pennsylvanian, Kansas, USA. Issue 1 (28th August 2020) - Leibach, Wade W.; Rose, Nick; Bader, Kenneth; Mohr, Laura J.; Super, Kristopher; Kimmig, Julien
Abstract: The uppermost Pennsylvanian Pony Creek Shale Lagerstätte (Pony Creek Shale Member, Wood Siding Formation, Wabaunsee Group) near Maple Hill, Wabaunsee County, Kansas, contains exceptionally preserved horseshoe crab (Xiphosura) fossils. Associated with these fossils is an ichnofauna that includes trace fossils assumed to be produced by xiphosurids, as well as coprolites and a few burrows. Of the trace fossils recovered from the Pony Creek Shale Member, 26 specimens represent the ichnogenera Arborichnus, Crescentichnus, Kouphichnium, and Selenichnites, all of which are commonly associated with xiphosurids. The other trace fossils consist of the ichnogenus Rhizocorallium, several unidentified burrows, and coprolites, some preserving animal remains. The xiphosuran locomotion traces from the Pony Creek Shale Member are primarily crawling trails. These trace fossils are distinguished by back and forth scratch imprints, as opposed to the typical xiphosurid tracks that show independent foot marks in the substrate. Other trace fossils include resting traces and feeding traces. Previous paleoenvironmental interpretations and the trace and body fossil record indicate a marginal-marine depositional system for the Pony Creek Shale.